2022
DOI: 10.36401/jipo-22-4
|View full text |Cite
|
Sign up to set email alerts
|

Oligometastatic Squamous Cell Transformation From Metastatic Prostate Adenocarcinoma Treated With Systemic and Focal Therapy: A Case Report

Abstract: Transformation to squamous cell carcinoma (SCC) after initial treatment of a primary prostate adenocarcinoma is rare and typically results in rapid treatment-refractory disease progression and death. Here, we present a case of a 70-year-old man who was initially treated with prostatectomy and radiotherapy, and later developed bone metastases. After commencing systemic therapy with androgen deprivation therapy (ADT) and apalutamide, his prostate-specific antigen (PSA) declined to undetectable levels, yet short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Squamous cell transformation associated with metastatic prostate cancer is a rare entity that accounts for less than 1% of all prostate malignancies [5]. Although there are a few case reports of squamous cell transformation to date, it has been more commonly seen in primary prostate adenocarcinoma rather than metastatic prostate adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Squamous cell transformation associated with metastatic prostate cancer is a rare entity that accounts for less than 1% of all prostate malignancies [5]. Although there are a few case reports of squamous cell transformation to date, it has been more commonly seen in primary prostate adenocarcinoma rather than metastatic prostate adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was CCND3 amplification and absence of the TMPRSS2::ETV4 fusion in the later specimen after hormonal therapy, which might suggest that CCND3 amplification and loss of the TMPRSS2::ETV4 fusion may be associated with squamous transformation. In a prior study, Autio and McBride showed loss of RNF43 in the squamous metastasis after initial ADT of a primary prostate adenocarcinoma [5]. Identifying the genetic changes with a molecular panel is very critical in guiding the systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation